COVID-19 and Sarcoidosis, Readiness for Vaccination: Challenges and Opportunities - Manansala, Michael; Chopra, Amit; Baughman, Robert P.; Novak, Richard; Lower, Elyse E.; Culver, Daniel A.; Korsten, Peter; Drake, Wonder P.; Judson, Marc A.; Sweiss, Nadera (Frontiers in Medicine, 2021)
Sarcoidosis is an immune mediated chronic inflammatory disorder that is best characterized by noncaseating granulomas found in one or more affected organs. The COVID-19 pandemic poses a challenge for clinicians caring for sarcoidosis patients who may be at increased risk of infection compared to the general population. With the recent availability of COVID-19 vaccines, it is expected that clinicians raise questions regarding efficacy and safety in sarcoidosis. However, studies examining safety and efficacy of vaccines in sarcoidosis are lacking. In this review, we examine the current literature regarding vaccination in immunocompromised populations and apply them to sarcoidosis patients. The available literature suggests that vaccines are safe and effective in patients with autoimmune disorders and in those taking immunosuppressive medications. We strongly recommend the administration of COVID-19 vaccines in patients with sarcoidosis. We also present a clinical decision algorithm to provide guidance on vaccination of sarcoidosis patients against COVID-19.